Space Whale
Artist and 24-Hour Mural Marathon contestant, Kendel Leslie, paints a colorful mural with a blue humpback whale as the primary subject. The whale is painted in several shades of blue and purple. The background is composed of different shapes formed in light pink, magenta, lime green, pastel yellow and purple among a black background with white stars, alluding to a galaxy-like ocean.